DNA-methylation-mediated silencing of miR-486-5p promotes colorectal cancer proliferation and migration through activation of PLAGL2/IGF2/β-catenin signal pathways. Issue 10 (October 2018) - Liu, Xiangxiang; Chen, Xiaoxiang; Zeng, Kaixuan; Xu, Mu; He, Bangshun; Pan, Yuqin; Sun, Huiling; Pan, Bei; Xu, Xueni; Xu, Tao; Hu, Xiuxiu; Wang, Shukui
Abstract As one of the most common cancers worldwide, colorectal cancer (CRC) causes a large number of mortality annually. Aberrant expression of microRNAs (miRNAs) is significantly associated with the initiation and development of CRC. Further investigations regarding the regulatory mechanism of miRNAs is warranted. In this study, we discovered that miR-486-5p was remarkably downregulated in CRC, which partially results from higher DNA methylation in the promoter region detected by using methylation-specific PCR, bisulfite sequencing PCR, and DNA demethylation treatment. Besides, decreased miR-486-5p was obviously associated with advanced TNM stage, larger tumor size, lymphatic metastasis, and poor prognosis in CRC. Upregulated miR-486-5p inhibited the proliferation and migration of CRC through targeting PLAGL2 expression and subsequent repressing IGF/β-catenin signal pathways both in vitro and in vivo. Notably, plasma miR-486-5p expression was significantly upregulated in CRC patients and we identified plasma miR-486-5p as a novel diagnostic biomarker of CRC using receiver operating characteristic (ROC) curve analysis. Moreover, exploration in GEO dataset revealed that circulating miR-486-5p is tumor derived through being packaged into secretory exosomes. Taken together, our data demonstrated that miR-486-5p promotes colorectal cancer proliferation and migration through activation of PLAGL2/IGF2/β-catenin signal pathway, which is a promising therapeutic target of CRC treatment.